RELATIONS OF GEODYNAMIC PROCESSES, TECTONIC STRESSES AND STRONG EARTHQUAKES ON THE MIDDLE KURIL FROM 2006 THROUGH 2009 WITH ERUPTION OF THE SARYCHEV PEAK VOLCANO - Timofei K. Zlobin; Anastasia Yu. Polets (Геодинамика и тектонофизика, 2015)
It is suggested that the eruption of the Sarycheva Peak volcano on 11 June 2009 may have been related to strong earthquakes which occurred in the Middle Kuril Islands from 2006 through 2009 (Figure 1), geodynamic processes (such as tectonic activation, subduction, and friction of contacting blocks), tectonic stresses, melting of rocks, rising of the melting substance, gases and fluids. The publication discusses the earthquake hypocenters profile along the Kuril Islands (Figure 2), the seismogeological depth profile of volcanoes of the Kuril Islands that was published by T.K. Zlobin (Figure 3), and positions of the magmatic chamber and the seismogenic zone of the SenHelens volcano from the publication by S. Carey (Figure 4).The map of earthquake epicenters for the Middle Kuril Islands is constructed on the basis of the NEIC catalogue (Figure 5). A corresponding depth profile showing earthquake hypocenters is constructed (Figure 6).An aseismic area is detected underneath the Matua Island (Sarychev Peak volcano); it is almost 30 km wide and about 200 km thick. In the Middle Kuril Islands, magma lifting and eruption were facilitated by stretching of the lithosphere (Figure 7), occurrence and activation of breaks, fractures and faults due to earthquakes which occurred from 2006 though 2009, and lifting of gas and fluids (Figure 8). The eruption was possible by explosion upon instant injection of fluids into the porous space due to considerable shear stresses, which occurred after the earthquakes, and the reaction of dehydration. It can also result from supply of volcanic gases and fluids, according to the vacuumexplosion fluid dynamics model.